Leadership for Success The Jamaican School Experience. - Hutton, Disraeli M. (University of the West Indies Press, 2017)
Leadership for Success is intended for a wide cross-section of educators, policymakers, educational planners, parents and the general readers who would like to learn how high-performing principals run schools effectively. The contributors offer vital lessons on the kinds of working relationships that are required among parents, school boards, communities, students, middle managers and the principals to make a difference in school performance.